Case Report: Successful late-line pralsetinib treatment in an ALK-rearranged lung adenocarcinoma patient with KIF5B-RET fusion resistant to alectinib - Jin, Feng; Wang, Chenyang; Yang, Fang; Wang, Shubin; Wang, Fen (Frontiers in Genetics, 2025)
Anaplastic lymphoma kinase (ALK) fusion, an oncogenic driver alteration, accounts for 5%–6% of non-small cell lung cancer (NSCLC) patients. ALK tyrosine kinase inhibitors (TKIs) provide significant clinical benefit in advanced ALK-rearranged NSCLC. However, acquired resistance to ALK TKIs inevitably arises, and the underlying mechanisms remain incompletely elucidated. This report describes a stage IV lung adenocarcinoma (LUAD) patient with ALK-rearranged who developed KIF5B-RET fusion-mediated resistance following second-line alectinib therapy. The patient achieved a partial response (PR) to third-line pralsetinib, sustained for 4 months. This case highlights KIF5B-RET fusion as a potential resistance mechanism post alectinib treatment and suggested = pralsetinib, a RET inhibitor, as a viable therapeutic option in this context. These findings contribute to the evolving understanding of resistance management strategies in ALK-rearranged NSCLC.